2019
DOI: 10.1021/acs.chemmater.8b04926
|View full text |Cite
|
Sign up to set email alerts
|

Area-Selective Atomic Layer Deposition Assisted by Self-Assembled Monolayers: A Comparison of Cu, Co, W, and Ru

Abstract: Area-selective atomic layer deposition (AS-ALD) is a promising "bottom-up" alternative to current nanopatterning techniques. Self-assembled monolayers (SAM) have been successfully employed as deactivating agents to achieve AS-ALD. In this work, the formation of octadecylphosphonic acid (ODPA) SAMs is studied on four technologically important metal substrates: Cu, Co, W, and Ru. The SAM quality is shown to be dependent on temperature, solvent, and the nature of the substrate. The blocking ability of the ODPA-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
181
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 144 publications
(188 citation statements)
references
References 67 publications
7
181
0
Order By: Relevance
“…Areas on the surface of the substrate can be activated using a catalytic reactant, electrons, or ion bombardment [89][90][91], allowing film growth only on the activated areas but not on the non-activated ones. Areas on the surface of the substrate can also be passivated using polymer films or self-assembled monolayers of organic molecules (SAMs) [92][93][94], which are often used to block areas of the surface where film growth is undesired. selectively adsorbed on the non-growth areas to block film growth on these areas.…”
Section: Area Selective Cvdmentioning
confidence: 99%
“…Areas on the surface of the substrate can be activated using a catalytic reactant, electrons, or ion bombardment [89][90][91], allowing film growth only on the activated areas but not on the non-activated ones. Areas on the surface of the substrate can also be passivated using polymer films or self-assembled monolayers of organic molecules (SAMs) [92][93][94], which are often used to block areas of the surface where film growth is undesired. selectively adsorbed on the non-growth areas to block film growth on these areas.…”
Section: Area Selective Cvdmentioning
confidence: 99%
“…Lithography is then performed on the blocking layer to obtain the desired pattern with growth and non-growth areas. The blocking layers are often self-assembly monolayers (SAMs) [139,140]. One challenge with using SAMs is that they may not be compatible with energetic co-reactants like ozone [141].…”
Section: Area-selective Atomic Layer Depositionmentioning
confidence: 99%
“…The selective deposition is quite complicated and relies on the coupled parameters, including substrates, precursors, temperature, pressure and aspect ratio dependency. Prior reports showed that the selectivity could be obtained by chemical modification, including surface passivation with polymers, self-assembled monolayers (SAMs), inhibitors and so on [15][16][17].…”
Section: Introductionmentioning
confidence: 99%